Hermite-Hadamard- and Jensen-Type Inequalities for Interval h1, h2 Nonconvex Function. (21st April 2020) - Bai, Hongxin; Saleem, Muhammad Shoaib; Nazeer, Waqas; Zahoor, Muhammad Sajid; Zhao, Taiyin
Abstract : In the present study, we will introduce the definition of interval h 1, h 2 nonconvex function. We will investigate some properties of interval h 1, h 2 nonconvex function. Moreover, we will develop Hermite-Hadamard- and Jensen-type inequalities for interval h 1, h 2 nonconvex function.